2013
DOI: 10.7314/apjcp.2013.14.6.3403
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Genes and SNPs Associated with Breast Cancer

Abstract: Breast cancer is the second killer cancer among American women after lung cancer (http://www.wwhf. org/hi_cancer_4.asp). Researches have shown that women with a family history of breast cancer have increased risk of developing breast cancer. The mutations responsible for increasing breast cancer risk within families are recognized. These include mutations in ATM,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…In our study about 30% of male with breast cancer had positive family history for some cancer. It is well known that carriers of BRCA1 and BRCA2 mutations are predisposed to high lifetime risk of breast cancer (Mahdi et al, 2013). Mutation in BRCA1 and BRCA2 gene in females also increased the risk of pancreatic cancer and other cancers, while in males it increased the risk of prostate cancer, pancreas cancer and breast cancer (Thompson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In our study about 30% of male with breast cancer had positive family history for some cancer. It is well known that carriers of BRCA1 and BRCA2 mutations are predisposed to high lifetime risk of breast cancer (Mahdi et al, 2013). Mutation in BRCA1 and BRCA2 gene in females also increased the risk of pancreatic cancer and other cancers, while in males it increased the risk of prostate cancer, pancreas cancer and breast cancer (Thompson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Single nucleotide polymorphisms (SNPs), located in coding or noncoding regions of a gene, occur most frequently among the diverse categories of genetic variation (Mahdi et al, 2013). Research has indicated that SNPs in miRNAs could be related to various types of tumors such as colorectal cancer (Kim et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that environmental risk factors such as lifestyle, hormonal and reproductive factors, and exposure to chemical carcinogens explain 30-50% of cases; hereditary factors such as high-penetrance susceptibility BRCA 1/2 mutations cause 5-10% of cases; and the other 40-65% can be attributed to unknown factors, such as gene-environment infteractions (Yoo et al, 2006;Park et al, 2009;Yanhua et al, 2012;Mahdi et al, 2013).…”
Section: Introductionmentioning
confidence: 99%